Insights on Prevalence of Hereditary Aortic Thoracic Disease and Impact on Family Screening in Routine Clinical Cardiothoracic Surgery Care - Simone Gasser; Michael Graber; Nikolaos Bonaros; Michael Grimm; Julia Dumfarth (Genes, 2026)
Objective: Heritable thoracic aortic disease (HTAD) is an important cause of thoracic aortic aneurysm and dissection, yet remains underdiagnosed. We aimed to summarize the prevalence of syndromic and non-syndromic HTAD, describe variants of uncertain significance (VUS), and evaluate the impact of family screening in a contemporary cardiothoracic surgical cohort. Methods: Between 2018 and 2026, 163 patients underwent genetic testing for suspected HTAD at our institution. A total of 139 patients with completed genetic testing were included in the analysis. Indications for testing included root aneurysm or acute aortic dissection before the age of 60 years with or without positive family history, aneurysms involving multiple vascular territories, or syndromic features suggestive of a heritable aortopathy. Results: The mean age at testing was 45.8 ± 15.1 years and 33% of patients were female. Aortic dissection represented the initial manifestation of disease in 40% of patients. Positive family history was present in 60% of patients. Pathogenic variants were identified in 24%. Twenty-three patients were diagnosed with syndromic HTAD, most commonly Marfan syndrome, while 10 patients were found to have non-syndromic HTAD. Variants of uncertain significance were detected in 27 patients (19%), predominantly affecting MYLK and MYH11. Following diagnosis, 87 relatives underwent screening, resulting in 18 prophylactic aortic operations. Conclusions: Cardiac surgeons should be aware of the importance of genetic testing in patients with aortic disease. Beyond the individual patient, the broader goal is to identify at-risk family members and prevent acute aortic syndromes. Continued collection of genotype–phenotype data is essential to improve interpretation of variants of uncertain significance and optimize future patient care.